Merawat Ingatan: Keterlibatan Publik dalam Pelestarian Monumen Perjuangan di Cibinong Bogor 1985-2020 - Dewita Alifah Firyal; Amirul Hadi (Socio Historica: Journal of Islamic Social History, 2022)
This study aims to determine the extent of public involvement, namely the community and government in the preservation of the historic building, the Cibinong Community Struggle Monument which is located in Cibinong which is the central government area of Bogor Regency. since its founding in 1985 to 2020 has experienced a decline in attention. Even though in today's technologically sophisticated era, the public can access a wide variety of information, including historical knowledge. So that the community has a role in the preservation of the monument that stands. Therefore, this study should be disclosed as an effort to preserve historic buildings in the future so that they are preserved and maintained. The method used is a historical study with a sociological and political approach, and the data presented is descriptive analytical. The results of this study indicate that there are several factors that influence the emergence of community involvement in the preservation of the Cibinong Monument. The first factor is historical awareness, which is still dominated by the families of fighters from the Cibinong Bivouac War. The second factor is the important role of the media in publishing news on the condition of the Monument for the image of the Cibinong area as the capital of Bogor Regency. It can be concluded that the public knows the general history of the Monument which is written on the Monument stone. In addition, the government's role in the process of implementing monument conservation is still passive and lacks initiative. So that the public's sense of belonging to the monument needs to be improved.Penelitian ini bertujuan untuk mengetahui sejauhmana keterlibatan publik dan pemerintah dalam pelestarian bangunan bersejarah, Monumen Perjuangan Masyarakat Cibinong yang berlokasi di Cibinong, Kabupaten Bogor. Metode yang digunakan merupakan kajian sejarah dengan pendekatan sosiologi dan politik, dan data akan disajikan secara deskriptif-analitis. Hasil dari penelitian ini menunjukkan bahwa terdapat beberapa faktor yang mempengaruhi munculnya keterlibatan masyarakat dalam pelestarian Monumen Cibinong. Faktor pertama adalah kesadaran sejarah yang masih didominasi oleh pihak keluarga pejuang dari Perang Bivak Cibinong. Faktor kedua adalah peran penting media dalam mempublikasikan berita kondisi Monumen untuk citra daerah Cibinong sebagai Ibukota Kabupaten Bogor. Dapat disimpulkan bahwa publik mengetahui sejarah Monumen secara umum yang tertera pada batu Monumen. Selain itu, peran pemerintah dalam proses pelaksanaan pelestarian monumen masih pasif dan kurang berinisiatif. Sehingga rasa memiliki publik terhadap monumen perlu ditingkatkan.